Organic anion transporter 1 is an HDAC4-regulated mediator of nociceptive hypersensitivity in mice - Litke, Christian; Hertle, Anna M.; Kenkel, Ann-Kristin; Paldy, Eszter; Lu, Jianning; Kuner, Rohini; Mauceri, Daniela (Nature Communications, 2022)
Persistent pain is sustained by maladaptive changes in gene transcription resulting in altered function of the relevant circuits; therapies are still unsatisfactory. The epigenetic mechanisms and affected genes linking nociceptive activity to transcriptional changes and pathological sensitivity are unclear. Here, we found that, among several histone deacetylases (HDACs), synaptic activity specifically affects HDAC4 in murine spinal cord dorsal horn neurons. Noxious stimuli that induce long-lasting inflammatory hypersensitivity cause nuclear export and inactivation of HDAC4. The development of inflammation-associated mechanical hypersensitivity, but neither acute nor basal sensitivity, is impaired by the expression of a constitutively nuclear localized HDAC4 mutant. Next generation RNA-sequencing revealed an HDAC4-regulated gene program comprising mediators of sensitization including the organic anion transporter OAT1, known for its renal transport function. Using pharmacological and molecular tools to modulate OAT1 activity or expression, we causally link OAT1 to persistent inflammatory hypersensitivity in mice. Thus, HDAC4 is a key epigenetic regulator that translates nociceptive activity into sensitization by regulating OAT1, which is a potential target for pain-relieving therapies.
Gesehen am 09.03.2022